Acorus shannai (Acoraceae), a new species from Southern China - Zhuo Cheng; Xinyu Liu; Nianting Yu; Weizhe Chen; Haofeng Zhao; Feifei Li; Chunlin Long (PhytoKeys)
Acorus shannai (Acoraceae) is a commonly used seasoning in southern China. It was previously misidentified as A. macrospadiceus (Yamam.) F. N. Wei & Y. K. Li before. Through comparison of morphological characteristics, distribution locations, and type specimen, we determined that the elevation of A. gramineus var. macrospadiceus Yamam to species status was incorrect. Therefore, we propose a formal description of a new species following nomenclature regulations. Based on morphological and plastid genomic data, this study formally describes and illustrates Acorus shannai, distributed in the Qiandongnan area of Guizhou Province and its surroundings, confirming it as a new species within the genus Acorus. This species is morphologically and phylogenetically distinct from other members of the A. gramineus group. Key distinguishing features include a strong fennel odor (vs. aromatic in “A. tatarinowii” and A. gramineus), fruit with prominent dorsal sutures (vs. inconspicuous dorsal sutures in “A. tatarinowii” and A. gramineus), and a leaf-shaped spathe that is about 2–3 times as long as the spadix (vs. more than 3 times in “A. tatarinowii”). Phylogenetic analysis showed that A. shannai is closely related to the other species in the A. gramineus group. The recognition of A. shannai is not only important for the species diversity and phylogenetic relationship of Acorus, but also can avoid the drug safety caused by using other Acorus species as A. shannai to eat and promote the conservation of A. shannai resources.